Kurikulum Merdeka Belajar: Analisis Prinsip dan Aksioma Pengembangan Kurikulum Pendidikan Agama Islam - Debi Fajrin Habibi (Program Studi Pendidikan Agama Islam, Universitas Majalengka, 2023)
The curriculum is one of the strategic components in the education system, therefore the curriculum must always experience development according to the demands of the times. Such development needs to be based on systematic and tested curriculum principles and axioms. The latest development of the national curriculum at this time is the initiation of the Merdeka Learning curriculum. This curriculum aims to encourage students to understand knowledge according to their field of expertise, so that they are ready to compete in the global arena. This article aims to analyze the relevance of the principles and values of the Merdeka Learning curriculum with the principles and axioms of the curriculum. The method used in this research is library research through content analysis. This study shows that theoretically the Merdeka Learning curriculum contains five general principles of curriculum development, namely: relevance, flexibility, continuity, efficiency, and effectiveness.